STRATEGI INTEGRATED MARKETING COMMUNICATION (IMC) UNTUK MENINGKATKAN LOYALITAS ANGGOTA BMT AMANAH UMMAH SUKOHARJO - Pritandhari, Meyta; M.Stats, Siswandari; Riani, Asri Laksmi (Jurnal Pendidikan Insan Mandiri, 2014)
The research is aimed to determine the strategy of Integrated Marketing Communication (IMC) is most effective in increasing customer loyalty of BMT Sukoharjo Amanah Ummah. This research used a descriptive research method with a qualitative analysis approach. Data collection techniques used was interview, observation, and documentation. The results of this research indicate that the five elements of the IMC strategy there is one element which is most effectively used to increase customer loyalty, namely personal selling strategy. Based on the results of the interview, it can be seen that personal selling is the most obtained information source by the customer of BMT. It is proved by 21 customers or 56.8 %. While the location factor is the fewest obtained information source that is 7 customers or 18.9 %. Personal selling strategies can increase customer loyalty, because it interacts with BMT directly. BMT marketing goes straight to the customers by providing good service so it can create a good context with the customers. This case can make close context between customers and BMT, therefore it will create loyalty. Thus, it can be concluded that personal selling strategies is the most effective to increase customer loyalty of BMT. Another advantage of personal selling strategy is it can be used in the long term that will strengthen the brand of BMT in society.Keywords  : Integrated Marketing Communication (IMC), Loyalty Members, Baitul Maal Wat Tamwil (BMT)